Primary Omental Torsion Mimicking Acute Appendicitis: An Unusual Cause of Acute Abdominal Pain in a Young Male - Mehmet Tolga Kafadar; Ismail Cetinkaya; Osman Bardakci (Eurasian Journal of Emergency Medicine, 2018)

(untitled)
Omental torsion is a very rare cause of acute abdomen. It commonly indicates itself with the symptoms and signs of acute appendicitis because of its localization on the right of the abdomen. The diagnosis is usually finalized by performing laparotomy or laparoscopy. Omental torsion may be primary or secondary, depending on omental cyst, tumor, intra-abdominal adhesions, or hernias. In this article, we present a 27-year-old male patient who underwent emergency surgery with a preliminary diagnosis of acute appendicitis and postoperatively diagnosed to have omental torsion. Considering omental torsion and different pathologies in patients with suspected clinical acute appendicitis, we are of the opinion that it would be useful to consider alternatives such as different surgical incisions and diagnostic laparoscopy.